The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/sea2.12114
|View full text |Cite
|
Sign up to set email alerts
|

Finance beyond function: Three causal explanations for financialization

Abstract: This article suggests that it is advantageous for social scientists to deliberately depart from functionalist theories seeking to explain the expansion of financial instruments and logics across social life. Rather, we identify three causes of financialization from three extant clusters of scholastic activity: an organic political economy that sees finance expanding as a product or by‐product of larger state‐ and imperial‐level political struggles, a relational sociology that sees the ways that finance expands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 102 publications
(94 reference statements)
0
11
0
Order By: Relevance
“…Thus economists do not just interpret the markets; they produce them by employing ideas, logics, models, and understandings of the economy in their work (MacKenzie et al 2007; Muniesa 2014). These approaches have informed anthropological studies of finance, which have shown how investment bankers, financiers, and currency participants understand markets and how they enact practices that help figure, shape, and create the economy (Ho 2009; Maurer 2005; Miyazaki 2013; Pitluck et al 2018; Zaloom 2006).…”
Section: Corporate Cultures and Capitalismmentioning
confidence: 99%
“…Thus economists do not just interpret the markets; they produce them by employing ideas, logics, models, and understandings of the economy in their work (MacKenzie et al 2007; Muniesa 2014). These approaches have informed anthropological studies of finance, which have shown how investment bankers, financiers, and currency participants understand markets and how they enact practices that help figure, shape, and create the economy (Ho 2009; Maurer 2005; Miyazaki 2013; Pitluck et al 2018; Zaloom 2006).…”
Section: Corporate Cultures and Capitalismmentioning
confidence: 99%
“…In this article, we highlight the ambiguities of this financialization, and we connect these ambiguities to the way that CCT is appropriated by beneficiaries in debt and credit relationships. We propose a way of thinking about financialization as a political project (see also Pitluck, Mattioli, and Souleles 2018) through the relational uses of finance in defining and structuring social relations. We analyze how the monthly income provided by the cash transfer program reorganizes household budgets and creates networks of sociality, and we highlight how financial relations are deeply connected to these networks.…”
Section: Conditional Cash Transfermentioning
confidence: 99%
“…The anthropological study of financialization has successfully ventured into investment banks, into central banks, and onto trading floors (Cetina 2003; Holmes 2009; Ortiz 2014; Zaloom 2006). However, when studying nonprofessional financial practices ethnographically, anthropologists have focused almost exclusively on microfinance and neighboring subject matter (Pitluck, Mattioli, and Souleles 2018; Weiss 2020). This methodological bipolarity, which divides expert knowledge and financialized subjects as two discrete fields of anthropological inquiry, becomes particularly problematic when theorizing small‐time speculators' motives, practices, and trajectories in finance capitalism.…”
mentioning
confidence: 99%